A study on pre-retting and post-retting water of waterbodies from a selected area of Bangladesh (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
The study was conducted to analyze the pre and post-retting water of five randomly selected ponds regarding the parameters viz. BOD5, COD, TSS, TDS, TKN, TP, CI, PH, Ec PH, and EC. BOD5 (ranging from 110 to 215 mg/l and 170 to 237 mg/l, respectively)and COD (227 mg/l to 310 and 299 to 403 mg/l, respectively)values of both pre and post-retting water of all the ponds were much higher than recommended values. Values of TSS, TKN, TP tests of both pre and post-retting water of the ponds reflected higher values than recommended values. Whereas, TDS(213 to 501 mg/l and 210 to 595 mg/l, respectively) and Cl (51 to 300mg/l and 50 to 305 mg/l, respectively) values were less than recommended values. PH values were within the recommended range of PH 6 to PH 9. All these results indicates that jute-retting is may not be the one and only factor to deteriorate the water quality of ponds. Jute-retting causes transitory water pollution in the water bodies only which can be minimized or removed by different ways. To find out specific way(s) to minimize or eradicate this transitory pollution further research is required.